CLINICAL AND METABOLIC CHARACTERISTICS OF ADOLESCENTS WITH METABOLIC SYNDROME IN THE REPUBLIC OF KARAKALPAKSTAN - Ermatov N.J., Jumanazarova A.J. (Central Asian Journal of Medicine, 2025)
Metabolic syndrome (MS) in adolescents is a growing challenge for public health systems, particularly in socially and environmentally vulnerable regions. The aim of this study was to assess the biochemical and anthropometric characteristics of adolescents with previously diagnosed MS living in the Republic of Karakalpakstan. A total of 157 schoolchildren aged 11 to 15 years were included, based on medical records from school health offices. Parameters of lipid profile, glucose metabolism, blood pressure, and somatic development were analyzed. The findings revealed a high prevalence of combined MS components: abdominal obesity, hypertension, hypertriglyceridemia, and low HDL-C. Sex-specific features and significant correlations between BMI, glucose, and blood pressure were identified. These results highlight the need for early detection and a multifactorial approach to the prevention of metabolic disorders in children and adolescents.